THE CONCEPT OF SCIENTIFIC AND TECHNICAL TEXT AND ITS LINGUISTIC FEATURES. (Ustozlar uchun, 2026)
This article examines the concept of scientific and technical texts and their linguistic features from a theoretical and applied linguistic perspective. The study analyzes lexical, grammatical, and stylistic characteristics that distinguish scientific discourse from other functional styles. Particular attention is given to terminology, objectivity, nominalization, and syntactic patterns typical of scientific communication. The research is based on descriptive and comparative methods, as well as a review of contemporary linguistic studies. The findings demonstrate that scientific and technical texts are characterized by precision, standardization, and a high degree of abstraction, which ensure effective knowledge transmission in professional contexts.